2015
DOI: 10.1186/s13017-015-0037-2
|View full text |Cite
|
Sign up to set email alerts
|

WSES position paper on vascular emergency surgery

Abstract: Trauma, both blunt and penetrating, is extremely common worldwide, as trauma to major vessels. The management of these patients requires specialized surgical skills and techniques of the trauma surgeon. Furthermore few other surgical emergencies require immediate diagnosis and treatment like a ruptured abdominal aortic aneurysm (rAAA). Mortality of patients with a rAAA reaches 85 %, with more than half dying before reaching the hospital. These are acute events demanding immediate intervention to save life and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 108 publications
(121 reference statements)
1
1
0
3
Order By: Relevance
“…Indeed, such an approach requires exceptional precision to avert complications like tension or stenosis, particularly when end-to-end anastomosis is considered. 27 Corroborating our findings, a similar study reported that primary repair was the most frequently utilized surgical procedure in 65% of patients, with end-to-end anastomosis and saphenous vein graft interposition applied in 44% and 38% of cases, respectively. 28 Additionally, a previous study recommended saphenous vein graft interposition as the most effective surgical intervention for injuries to the superficial femoral artery.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, such an approach requires exceptional precision to avert complications like tension or stenosis, particularly when end-to-end anastomosis is considered. 27 Corroborating our findings, a similar study reported that primary repair was the most frequently utilized surgical procedure in 65% of patients, with end-to-end anastomosis and saphenous vein graft interposition applied in 44% and 38% of cases, respectively. 28 Additionally, a previous study recommended saphenous vein graft interposition as the most effective surgical intervention for injuries to the superficial femoral artery.…”
Section: Discussionsupporting
confidence: 85%
“…Adicionalmente massagem cardíaca, vigorosa pode promover dissolução de ar já presente nas artérias coronárias. A aspiração da raiz da aorta é feita para evacuar qualquer bolsa de ar acumulada (31).…”
Section: Controle Da Embolia Aérea Broncovenosaunclassified
“…Quando for necessário a visualização de ferimentos penetrantes no arco aórtico ou ramos principais da aorta, esternotomia mediana pode ser necessária e nos caos de lesão do arco aórtico, circulação extra-corpórea deve estar pronta para utilização (31). Na ocasião do esterno ser dividido transversalmente, os vasos torácicos internos devem ser ligados quando a perfusão for restaurada; isto pode ser realizado utilizando-se um ponto em "X" com seda ou algodão 2-0.…”
Section: Incisão Torácicaunclassified
“…The permissive hypotension concept aims to reduce the fluid supply in rAAA patients with shock, since massive fluid delivery leads to hemodilution, adversely affecting oxygenation, blood clotting, bleeding due to increased pressure, and thrombus detachment. The aim of preprocedural shock treatment is to provide only enough fluids to maintain a conscious patient, prevent ST changes in the ECG, and maintain the systolic blood pressure at 70-80 mm Hg [42] until surgical control of the bleeding is assured; however, the concept of preprocedural permissive hypotension in patients with rAAA (a patient clientele with high cardiovascular morbidity) is not clearly established. No randomized trials pertaining to this concept could be found in a Cochrane review, leaving the question open as to benefits for rAAA patients [92].…”
Section: Treatment Of the Raaamentioning
confidence: 99%